Are Adolescent Treatment Studies of Eating Disorders Utilizing Clinically Relevant Samples? A Comparison of RCT and Clinic Treatment‐Seeking Youth with Eating Disorders. (11th March 2013) - Stiles‐Shields, Colleen; Goldschmidt, Andrea B.; Lock, James; Le Grange, Daniel
Abstract: Objective: To assess potential selection bias in participant recruitment for randomized controlled trials (RCTs) of adolescent eating disorders (EDs), we compared participants recruited for RCTs evaluating psychosocial treatments with individuals seeking fee‐for‐service outpatient ED treatment [clinic treatment‐seeking (CTS)]. Method: Participants were 214 adolescents presenting to an outpatient ED research‐clinical program (92.1% female; M age = 15.4 ± 1.8 years). ANOVA and chi‐square tests assessed differences between CTS participants and those presenting for no‐cost treatment through RCTs. A secondary analysis compared RCT participants to participants eligible for the RCTs that opted for fee‐for‐service treatment. Results: RCT participants had greater baseline ED and general psychopathology ( p  < .001); however, CTS participants were more likely to present with a comorbid psychiatric disorder ( p  < .05) and higher family income ( p  < .05). Discussion: Results suggest that RCT participants did not have less pathology than CTS participants. While preliminary, results do not indicate a systematic population bias in selecting healthier patients for RCTs involving adolescent ED. Copyright © 2013 John Wiley & Sons, Ltd and Eating Disorders Association.